Saus Cocolan Pepaya Sehat sebagai Inovasi Pangan bagi Masyarakat di Kampung Wisata Rhepang Muaif, Kabupaten Jayapura - Henderina J. Keiluhu; Gerardinalia Ngamelubun; Evie L. Warikar; Jeirel Wattilete; Raini Panjaitan; Yelsi Y. Palebangan; Seramina R.T. Sawegu (Jurusan Biologi FMIPA Universitas Cenderawasih, 2025)
Papaya (Carica papaya L.) is a fruit with high nutritional value and significant potential to be developed into various processed food products. However, its utilization in the communities remains limited as papaya is generally consumed fresh or processed into simple dishes such as juice and vegetables. This community service activity aimed to increase public knowledge and skills in diversifying papaya-based food products by introducing the processing of papaya into a healthy dipping sauce that is free from artificial sweeteners and preservatives. The activity also sought to increase awareness of the economic potential of papaya-based processed products. It was conducted on August 9, 2025, in collaboration with the local community of Rhepang Muaif Tourism Village, at the kitchen pavilion of Isyo Hills Bird Watching Campsite. A total of 13 participants were involved, consisting of 8 youths, 3 middle-aged adults, and 2 elderly individuals. The implementation methods included socialization, hands-on training, and direct assistance in the preparation. The training utilized simple methods, common kitchen tools, and easily accessible ingredients. The results showed that participants were able to produce a spicy and healthy papaya-based dipping sauce that can be consumed with various snacks, such as boiled sweet potatoes, boiled bananas, fried bananas, and french fries. The product demonstrates potential economic value due to its affordability, health benefits, and marketability. Overall, the activity was well received, with participant satisfaction rates of 100%, indicating a positive response, successful implementation, and benefit to the community.